Fitness Costs and Benefits of Female Song - Michelle L. Hall (Frontiers Research Topics, 2017)
Bird song, traditionally regarded as primarily a male trait, is in fact widespread among female songbirds and was probably present in the ancestor of modern songbirds (Odom et al 2014 Nature Communications). These recent findings challenge the view that sexual dimorphism in the expression and complexity of song is largely the outcome of sexual selection on males. It is now clear that understanding the evolution of bird song requires explaining variation within and among species in the expression and complexity of female song. To do this, we need a better understanding of the nature of variation in female song in different contexts and systems, as well as the fitness costs and benefits of variation in the expression and complexity of female song. This Research Topic draws together current research on female song with the goal of understanding the fitness costs and benefits of the diversity of female singing behaviour apparent among songbirds. It includes articles ranging from single-species studies investigating how female song varies with context and contrasts with male song, to comparative analyses exploring relationships between female song and ecological, social, and other factors, as well as opinion pieces.